TEACHER PERCEPTION OF MULTICULTURAL CLASSROOM MANAGEMENT IN SINGKAWANG: QUALITATIVE RESEARCH IN INDONESIA’S MOST TOLERANT CITY - Muzammil, Ahmad Rabiul; Mariyadi, Mariyadi (JURNAL EDUSCIENCE, 2025)
Purpose: Teachers' attitudes towards multicultural classroom management determine civic education in multicultural classrooms. Therefore, this study aims to examine teachers' perceptions of managing multicultural classrooms in Singkawang, a city known for its high tolerance in Indonesia.Methodology: A qualitative research design was employed, utilizing semi-structured interviews to collect data from eight teachers (four male and four female) aged 32 to 52 years, representing Dayak, Melayu, and Javanese ethnicities. These teachers, working at primary and junior high schools, taught subjects such as Indonesian language, general classroom topics, and science. Purposive sampling was used to select participants, ensuring diverse cultural representation. Data collection occurred over October-November 2024, with interviews conducted in Indonesian and transcribed for thematic analysis based on Braun and Clarke's framework.Findings: Thematic analysis revealed six major themes: flexible classroom management, development of tolerance values, development of unity values, development of equitable services, utilization of local culture and wisdom, and Collaboration between students with different cultural backgrounds. Teachers reported the importance of adapting pedagogical approaches and curriculum content to accommodate diverse cultural needs, creating an inclusive and respectful learning environment.Significance: This study benefits educators, school administrators, and policymakers by providing insights into effective strategies for managing multicultural classrooms. It offers a practical framework to enhance cultural understanding, tolerance, and unity, contributing to the broader goals of multicultural education and social cohesion in diverse communities.